Relationship between core stability and Functional Movement Screening test in athletes - Bahiraei, Saeid; Sharbatzadeh, Reza; Nouri, Mohammad (Akademia Wychowania Fizycznego w Poznaniu)
Introduction and Aim. Functional Movement Screening (FMS™) tests provide beneficial information regarding the movement and stability in the kinetic chain. The core region of the body, as the basis of movement chain, accounts for the facilitation of force and torque transmission. The aim of the present study was to investigate the relationship between functional movement screen composite scores and core stability muscles endurance in athletes. Material and Methods. Forty-five male athletes with FMS scores ≤14 (LoFMS) and forty-five male athletes with FMS scores >14 (HiFMS) were studied. Stability of core muscles of the participants was investigated and compared using the McGill’s test. Results. The results of this study showed a significant difference in the mean stability of the anterior trunk muscles (p = 0.001), right side trunk muscles (p = 0.005) and left side trunk muscles (p = 0.001) between the athletes with LoFMS and HiFMS scores. Muscles’ endurance in the group with HiFMS score was significantly higher than the group LoFMS score (p = 0.001). However, there was no significant difference in the mean stability of the posterior trunk muscles between the two groups. In general, a significant difference was found between sum of core stability scores obtained from lumbar-pelvic stabilizer muscles in the posterior, anterior and lateral sides of athletes LoFMS and HiFMS scores. Conclusions. The results of this study showed that weakness in core stability can have a negative influence on movement patterns
Keywords: Functional Movement Screening (FMS™); core stability; movement pattern